Literature Review: Analysis of Factors Associated with the Incidence of Pneumonia in Toddlers (Age > 12-59 Months) - Irmae Irmae; Edi Hartoyo; Meitria Syahadatina Noor; Mohamad Isa; Roselina Panghiyangani (Indonesian Journal of Global Health Research, 2026)
Pneumonia is a major cause of infant mortality in Indonesia. Pneumonia is influenced by intrinsic and extrinsic factors, such as immunization status, exclusive breastfeeding, nutritional status, home environment, and family socioeconomic status. Objective to analyze factors associated with the incidence of pneumonia in toddlers (aged > 12-59 months) through a literature review. Literature review of national journals published between 2021 and 2025. Databases from Google Scholar and PubMed with keywords "pneumonia in toddlers, pneumonia in toddlers case-control, risk factors for pneumonia in toddlers". Data were collected through searches of relevant accredited journals and then analyzed descriptively to identify general patterns of risk factors, including intrinsic variables (age, gender, immunization status, exclusive breastfeeding, low birth weight (LBW), nutritional status) and extrinsic variables (home ventilation, exposure to cigarette smoke, economic status, maternal education, and access to health services). The most dominant and consistent factors associated with pneumonia in toddlers include: incomplete immunization status, lack of exclusive breastfeeding, low birth weight (LBW) and preterm birth, unhealthy housing conditions (poor ventilation, high crowding, and exposure to cigarette smoke), poor nutritional status, and maternal education and low access to health services. The incidence of pneumonia in toddlers in Indonesia is the result of an interaction between individual, environmental, and economic factors.